Effect of Pore Size on Cell Behavior Using Melt Electrowritten Scaffolds - Han, Yu; Lian, Meifei; Wu, Qiang; Qiao, Zhiguang; Sun, Binbin; Dai, Kerong (Frontiers in Bioengineering and Biotechnology, 2021)
Tissue engineering technology has made major advances with respect to the repair of injured tissues, for which scaffolds and cells are key factors. However, there are still some issues with respect to the relationship between scaffold and cell growth parameters, especially that between the pore size and cells. In this study, we prepared scaffolds with different pore sizes by melt electrowritten (MEW) and used bone marrow mensenchymal stem cells (BMSCs), chondrocytes (CCs), and tendon stem cells (TCs) to study the effect of the scaffold pore size on cell adhesion, proliferation, and differentiation. It was evident that different cells demonstrated different adhesion and proliferation rates on the scaffold. Furthermore, different cell types showed differential preferences for scaffold pore sizes, as evidenced by variations in cell viability. The pore size also affected the differentiation and gene expression pattern of cells. Among the tested cells, BMSCs exhibited the greatest viability on the 200-μm-pore-size scaffold, CCs on the 200- and 100-μm scaffold, and TCs on the 300-μm scaffold. The scaffolds with 100- and 200-μm pore sizes induced a significantly higher proliferation, chondrogenic gene expression, and cartilage-like matrix deposition after in vitro culture relative to the scaffolds with smaller or large pore sizes (especially 50 and 400 μm). Taken together, these results show that the architecture of 10 layers of MEW scaffolds for different tissues should be different and that the pore size is critical for the development of advanced tissue engineering strategies for tissue repair.